Boundedly rational backward induction - Shaowei Ke (Theoretical Economics, 2019)
This paper proposes simple axioms that characterize a generalization of backward induction. At any node of a decision tree, the decision maker looks forward a fixed number of stages perfectly. Beyond that, the decision maker aggregates continuation values according to a function that captures reasoning under unpredictability. The model is uniquely identified from the decision maker's preference over decision trees. Confronting a decision tree, the decision maker iteratively revises her plan for the future as she moves forward in the decision tree. A comparative measure of unpredictability aversion and several examples are discussed.
Keywords: D00; 330; Dynamic choice; imperfect foresight; time inconsistency